Sinergi Corporate Social Responsibility (CSR) PT Astra International Tbk Dalam Keberlanjutan Lingkungan Melalui Program Astra Green Company Khususnya Keanekaragaman Hayati - Januar Fahri Triwibiansyah; Ida Bagus Ketut Bayangkara (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses the synergy between the Corporate Social Responsibility (CSR) program of PT Astra International Tbk and environmental sustainability efforts through the Astra Green Company (AGC) program. PT Astra International Tbk, as the largest automotive company in Southeast Asia, demonstrates a strong commitment to environmental preservation through various initiatives, such as biodiversity conservation, energy efficiency, and waste reduction. This study employs a qualitative approach through literature review to analyze the contribution of AGC to environmental sustainability. The results show that programs such as Astra for a Green Indonesia and Pranaraksa have had a positive impact on the environment and increased public awareness of the importance of conservation. These initiatives not only strengthen the company’s image but also contribute to the achievement of the Sustainable Development Goals (SDGs). This article provides an important contribution to enriching the understanding of CSR’s role in supporting environmental sustainability and can serve as an inspirational model for other companies in Indonesia.